The Influence of Online Learning on Physics Learning Outcomes During The Covid-19 Pandemic - Suhariyono Suhariyono; Heri Retnawati (Radiasi : Jurnal Berkala Pendidikan Fisika, 2022)
Throughout the COVID-19 pandemic, it is hoped that all elements of education can still facilitate learning so that children remain active even though they are online. The Indonesian policy of the government in dealing with the spread of the COVID-19 outbreak is to prevent it by imposing social distancing. This policy impacts all lives, Education is one of them., especially in the online learning process. Physics is one of the specialization subjects given to high school students. The purpose of this research is to determine impact of online learning Physics on student learning outcomes and the things that affect this impact. This type of research is a mixed-method—qualitative data obtained by observation, documentation, and interview techniques. Quantitative data comes from evaluating student achievement before the application of online learning (before the pandemic) and after the implementation of online learning (during the pandemic). Participants in this quantitative study were 116 students, and qualitative participants were 5 students' parents. The result of this study is that there is a significant impact or difference between the effects of learning Physics before and after the pandemic. This can be seen from the effects of Pillai's trace, Wilks lambda, Hoteling's trace, and Roy's most enormous root test results stating that the significance value at 0.000 is smaller than 0.05. It can also be seen from the average before the pandemic, 80,04 and after the pandemic, 82.11 This is caused by that there is excessive parental participation in completing each student's task at home.